Size characterisation method and detection enhancement of plasmonic nanoparticles in a pump–probe system - Fuentes-Domínguez, Rafael; Smith, Richard J.; Pérez-Cota, Fernando; Marques, Leonel; Peña-Rodríguez, Ovidio; Clark, Matt (MPDI, 2017)
The optical resonance of metal nanoparticles can be used to enhance the generation and detection of their main vibrational mode. In this work, we show that this method allows the accurate characterisation of the particle’s size because the vibrational frequency of plasmonic nanoparticles only depends on their mechanical properties. Moreover, by a careful selection of the particle size and/or probe laser wavelength, the detected signal can be increased by a large factor (∼9 for the particles used in this work) under the same illumination conditions. Finally, we show experimentally that particles of different sizes inside the point spread function can be observed due to the differences in their vibrational states, which could provide a feasible route to super-resolution.